1987
DOI: 10.1007/bf01418459
|View full text |Cite
|
Sign up to set email alerts
|

FTIR-ATR spectroscopic determination of the distribution of surfactants in latex films

Abstract: FTIR-ATR (Fourier Transform Infra-Red-Attenuated Total Reflection) has been used to analyze the surface composition of coalesced acrylic latex films. The behavior of two anionic surfactants has been characterized. It has been found that surfactant distribution depends on the nature of the surfactant. A comparison between the normalized absorbance in transmission and in reflection has shown an enrichment of surfactants at the surfaces of films with a coalescence time of 3 days. The surfactant concentration at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 22 publications
0
59
0
1
Order By: Relevance
“…A very similar F ET value (0.14) was found when the films were prepared factant in latex films. [28][29][30][31][32] One key factor is the miscibility of the surfactant with the latex polywith 1 : 1 Phe-labeled soft particles and An-la8q4f 9705013 / 8Q4F$$5013 03-02-98 09:14:10 polpas W: Poly Physics normally under the influence of heat. In their experience, membranes formed from traditional low-molar-mass surfactants fragment during the drying process to a sufficient extent that newly dried films will not resorb D 2 O.…”
Section: Fluorescence Decay Profilesmentioning
confidence: 99%
“…A very similar F ET value (0.14) was found when the films were prepared factant in latex films. [28][29][30][31][32] One key factor is the miscibility of the surfactant with the latex polywith 1 : 1 Phe-labeled soft particles and An-la8q4f 9705013 / 8Q4F$$5013 03-02-98 09:14:10 polpas W: Poly Physics normally under the influence of heat. In their experience, membranes formed from traditional low-molar-mass surfactants fragment during the drying process to a sufficient extent that newly dried films will not resorb D 2 O.…”
Section: Fluorescence Decay Profilesmentioning
confidence: 99%
“…Zhao and co-workers (18,19) have shown by XPS, SIMS, and FTIR-ATR that films from MMA-BMA latexes prepared using the same surfactant as in the present work (sodium dodecyl diphenylether disulfonate, SDED) or sodium dodecyl sulfate (SDS) have different behaviors: in the case of SDS, they observed an enrichment of surfactant at the film-air and filmsubstrate interfaces during the film maturation. This is expected because the surface active agents lower the interfacial tension at the polymer/air and polymer/substrate interfaces.…”
Section: Introductionmentioning
confidence: 73%
“…It can be concluded that, in the case of conventional surfactant‐based films, the water forms a second phase in the polymer, but does not interact directly with the macromolecules (no plasticizing effect). Some authors have shown that during the film formation process, the surfactant molecules can migrate to form domains at the surface and in the film 11, 12. These highly hydrophilic domains are able to trap a large amount of water when the film is hydrated, without any plasticizing effect.…”
Section: Resultsmentioning
confidence: 99%